Students’ Perception of Mobile Assisted Language Learning in ESP classroom at Higher Education - Pamungkas, Zakaria Bintang (ELITE JOURNAL, 2026)
Digital learning has become a potential learning tool since the COVID-19 pandemic that has caused the use of new technologies including mobile assisted language learning (MALL). Meanwhile, the implementation of MALL in English language learning particularly ESP still has different challenges due to technical, instructional and financial barriers. Several previous research suggest exploring more teaching experiences related to the use of mobile assisted language learning for the next contribution. This research aimed to find out the students’ perception on the use of Mobile Assisted Language Learning at ESP class. It employed a descriptive qualitative method. It was conducted at ESP class in Islamic Religious Education (PAI) Study Program of Faculty of Tarbiyah at IAI Riyadlotul Mujahidin Ponorogo with enclose 15 students as a sample of this research. This research used the purposive sampling technique to take the sample. The data were collected through questionnaire and interview. To collect the data, the study employed the questionnaire with 10 items given to 15 students. The responses from the interview were concluded to answer the research questions. As a result of the study, it is shown that most of the students agree of using mobile assisted language learning for learning English in ESP class. By using MALL as medium of learning ESP in the class, it can increase students’ English ability with appropriate English standard, motivate them to learn English, improve their confidence to speak and to write in English, help them to comprehend English textbook or article, and assist them to understand the international standardized text.